2015
DOI: 10.17261/pressacademia.2015211508
|View full text |Cite
|
Sign up to set email alerts
|

A study for the interaction between risk premiums and stock exchange in developing countries

Abstract: This study attempts to examine the interaction of credit default swap (CDS), which stands for risk premium, with the stock exchanges of developing countries. To this end, 5-year CDS premiums belonging to Turkey, Argentina, Brazil, Indonesia, Malaysia, and China were obtained on a daily basis between April 2009 and April 2014 and were compared with stock exchange index closes in the same period. Data were analyzed via regression curve estimation models. Insignificant relationships were found between CDS premium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
(1 reference statement)
1
1
0
1
Order By: Relevance
“…The results are consistent with theoretical assumptions in most of the cases. The coefficients found related to the variables and direction of the relationships are in parallel with the studies conducted by Pan and Singleton (2008), Longstaff et al (2011), Liu and Morley (2012), Ertugrul and Ozturk (2013), Hanci (2014), Eren and Basar (2016), Basarir and Keten (2016), Yenice and Hazar (2015), Akkaya (2017), Munyas (2018) and Sadeghzadeh (2019).…”
Section: Tablesupporting
confidence: 81%
See 1 more Smart Citation
“…The results are consistent with theoretical assumptions in most of the cases. The coefficients found related to the variables and direction of the relationships are in parallel with the studies conducted by Pan and Singleton (2008), Longstaff et al (2011), Liu and Morley (2012), Ertugrul and Ozturk (2013), Hanci (2014), Eren and Basar (2016), Basarir and Keten (2016), Yenice and Hazar (2015), Akkaya (2017), Munyas (2018) and Sadeghzadeh (2019).…”
Section: Tablesupporting
confidence: 81%
“…A causality relationship between the CDSs and Euro bond was detected. Yenice and Hazar (2015) used correlation analysis to examine the relationship between the stock exchange, exchange rate, and CDS premium, focusing on developing countries (including Turkey) from 2009 to 2014. The results showed that the CDS premium correlates with the stock exchanges and exchange rates of countries.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Faiz ve USD kurunun CDS üzerindeki etkisi incelendiğinde ise Çin'de USD kuru etkisinin Faiz oranına göre daha fazla olduğu, Rusya'da ise Faiz oranının etkisinin USD kuruna göre daha fazla olduğu görülmüştür. Türkiye'de ise Faiz oranının etkisi yok denecek kadar az olmasına rağmen USD kurunun etkisinin olduğu tespit edilmiştir.Yapılan analizdeki bulgular, Longstaff & diğerleri (2011), Yenice & Hazar (2015), Liu & Morley (2012), Başarır & Keten (2016)'in çalışmalarını Türkiye için doğrular niteliktedir fakat incelenen diğer ülkeler için faiz oranı etkisinin de önemli olduğuna dair kanıtlara ulaşılmıştır.…”
Section: Sonuçunclassified